First report of perforation of ligamentum flavum by sequestrated lumbar intervertebral disc - Ozdemir, Bulent (J Craniovertebr Junction Spine, 2017)
Disc fragments are well known to migrate to superior, inferior, or lateral sites in the anterior epidural space, posterior epidural migrated lumbar disc fragments is an extremely rare disorder, 61 cases have been reported to date. However, there were no cases with perforated ligamentum flavum (LF). We report a different case with perforation of ligamentum ligamentum by disc fragment. To the best of our knowledge, this is the first report of perforation LF by a posterior epidural migrated sequester disc.